Developing a Technology-Enhanced Digital Counseling Model to Improve Students' Learning Comfort and Happiness - Gading, I Ketut; Sudarma, I Komang; Lestari, Luh Putu Sri; Rismawan, Kade Sathya Gita; Putri‎, Dewi ‎Arum Widhiyanti Metra; Dewi, Deshinta A; Lyesmaya, Dyah (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to develop and test a digital counseling model that integrates Mindfulness Cognitive Behavioral Harmony (MCBH) with digital tools to enhance students’ learning comfort and happiness in educational contexts. Methodology: A Research and Development design using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) was employed. Data were collected through questionnaires assessing model validity, practicality, learning comfort, and learning happiness from 280 elementary school students in Bali, Indonesia. The data were analyzed using descriptive and inferential statistics to determine the effectiveness of the model. Main Findings: The study found that the MCBH digital counseling model significantly enhanced students’ emotional regulation, learning comfort, and happiness. The digital tools used, including mobile applications and online platforms for mindfulness exercises and cognitive behavioral therapy techniques, were highly effective in providing accessible, continuous emotional support. This technology not only complemented traditional counseling methods but also contributed to the learning process by fostering sustained engagement, improved focus, and enhanced academic performance, showing how digital platforms can serve a pedagogical function in education. Novelty/Originality of this study: This study introduces a digital counseling model integrating mindfulness, cognitive behavioral therapy, and local cultural wisdom (Tri Hita Karana). It demonstrates how digital tools enhance emotional regulation, student engagement, and learning outcomes through continuous support and real-time feedback. The model contributes to educational technology by offering a scalable, sustainable, and culturally responsive approach to student well-being and learning support.